Interdisciplinarity in action: developing students’ soft skills through project-based learning and field work - Vasconcelos, Sandra (2022)
Recently, much due to the growth of the industry, tourism professionals are increasingly being challenged to develop new skills and adapt to dynamic markets, requiring them to be flexible, creative and, particularly after the recent COVID-19 pandemic, resilient. Mirroring these changes, Higher Education Institutions (HEI), and more specifically Tourism Higher Education (THE), are increasingly becoming aware of the need to rethink and further expand their programs, not only to make them more diverse and inclusive, but also meet current demands, particularly concerning the development of tourism graduates’ soft skills. Focusing on a project carried out at the School of Hospitality and Tourism (Vila do Conde, Portugal), this paper aims to describe an innovative interdisciplinary approach that combines academic and technical knowledge with the development of (inter)personal transferable skills, by challenging students to complete a collaborative assignment on different industry subsectors. Involving five different courses and facilitators, this assignment followed a Project-based Approach (PbL), having challenged students to carry out field work to collect stakeholders’ perceptions on what they considered to be the most important soft skills within the industry, most particularly in the Entertainment/Events, Travel Agencies/Tour Operators, Destination Marketing Organizations (DMO) and Accommodation subsectors. Framed by a literature review, the data and ensuing analysis were compiled and put forward in a short paper, that was publicly presented and discussed. Working in groups of 3 to 6 members, students conducted a total of 45 interviews, which resulted in 13 short papers, all of which identifying key soft skills and reflecting on how they can be developed. In addition to describing the rationale behind the project and its implementation, this paper will address the affordances and potential of interdisciplinarity in tourism education, not only by reflecting on the project’s outcomes, but also on participants’ expectations and final perceptions. Drawing from two questionnaires and unstructured observation, it is, therefore, expected to further advance recent research in innovative practices in Tourism Education, as well as provide other educators a case study that can support similar initiatives and projects.